2009
DOI: 10.1590/s0066-782x2009001100015
|View full text |Cite
|
Sign up to set email alerts
|

O efeito da musicoterapia na qualidade de vida e na pressão arterial do paciente hipertenso

Abstract: SummaryBackground: Arterial Hypertension (AH) is a mass disease, with consequences for the cardiocirculatory system, since its complications raise the rates of morbidity and mortality. Controlling blood pressure (BP) reduces complications and may preserve the quality of life (QOL) of patients. Studies show positive effects of music therapy as an adjuvant in the treatment of several diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
19

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 4 publications
1
15
0
19
Order By: Relevance
“…We found only two papers 11,16 which investigate directly the music and its effects on blood pressure, demonstrating a lack of studies related to the topic. Moreover, in five studies 10,17-20 , we found no statistically significant difference (p<0.05) on changes in blood pressure.…”
Section: Musical Stimulation and Cardiovascular System Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…We found only two papers 11,16 which investigate directly the music and its effects on blood pressure, demonstrating a lack of studies related to the topic. Moreover, in five studies 10,17-20 , we found no statistically significant difference (p<0.05) on changes in blood pressure.…”
Section: Musical Stimulation and Cardiovascular System Resultsmentioning
confidence: 98%
“…Other variables such as QOL in individuals with hypertension 11 , pain relief in cancer patients 17,21 , reduced anxiety 19 and factors such as levels of anesthetics in surgical patients 10,19,20,22 , post-traumatic stress associated with musical 16 , induced coma situations 23 and influence of music on musicians and no musicians 24 were also targets of selected articles in this review. The studies analyzed investigated responses to different musical styles, namely, slow classical music, fast classical music, twelvetone music, Techno, rap and raggae music, in individuals of both sexes, with ages ranging from one day of birth, past children aged four to 16 years, young graduates, to 65-year-old seniors.…”
Section: Musical Stimulation and Cardiovascular System Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Estudos explicam que esta influência é percebida por um modelo denominado integração neuro-visceral, onde existe uma interação entre os sistemas de controle da homeostasia que determina o fluxo nervoso autonômico controlador dos órgãos viscerais, levando a alterações em diversas funções fisiológicas 27 . Além disso, alguns autores demonstraram que uma intervenção com música foi capaz de reduzir a PA de repouso em pacientes tratados por meio de um programa de atendimento multiprofissional 28 . No entanto, além do fato de que, caso esta influência tenha existido em nosso estudo, pôde ser obtida nas duas sessões experimentais, uma vez que o VGS também apresentou a utilização da música, tornando homogêneo os resultados.…”
Section: Discussionunclassified
“…Music has been used in health, not only as a promotional tool, but also for treatment of injuries and to emphasize the comfort of terminally ill patients, as it promotes well-being, autonomy and expression of emotions 6 . In addition, this powerful art positively impacts the quality of life of health services users and may even influence blood pressure control and chronic pain 7,8 .…”
Section: Introductionmentioning
confidence: 99%